2007
DOI: 10.1103/physrevd.76.036004
|View full text |Cite
|
Sign up to set email alerts
|

Diquark and light four-quark states

Abstract: Four-quark states with different internal clusters are discussed within the constituent quark model. It is pointed out that the diquark concept is not meaningful in the construction of a tetraquark interpolating current in the QCD sum rule approach, and hence existing sum-rule studies of fourquark states are incomplete. An updated QCD sum-rule determination of the properties of diquark clusters is then used as input for the constituent quark model to obtain the masses of light 0 ++ tetraquark states (i.e. a bo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 82 publications
2
37
1
Order By: Relevance
“…However, there is no direct correspondence between the constituent quark picture and the operator (current) quark picture. Diquarks are thus not a meaningful concept in sum rule approaches [1134], and care must be taken not to overinterpret the results. Brito et al found that the mesons decay constants and hadronic couplings are consistent with a tetraquark structure for the light scalar mesons [1135].…”
Section: A Low-mass Nonet Of Scalar Mesonsmentioning
confidence: 99%
“…However, there is no direct correspondence between the constituent quark picture and the operator (current) quark picture. Diquarks are thus not a meaningful concept in sum rule approaches [1134], and care must be taken not to overinterpret the results. Brito et al found that the mesons decay constants and hadronic couplings are consistent with a tetraquark structure for the light scalar mesons [1135].…”
Section: A Low-mass Nonet Of Scalar Mesonsmentioning
confidence: 99%
“…The quantitative calculations of hadronic properties run into arduous difficulties. However, one can apply the QCD sum rule method [15] (for reviews see [16][17][18][19] and references therein), which is a nonperturbative formulation firmly based on QCD basic theory and has been successfully employed to research some light four-quark states [20][21][22][23][24][25]. In this work, we are devoted to predicting masses of Z + s1 and Z + s2 from QCD sum rules.…”
mentioning
confidence: 99%
“…We take the updated values of the diquark masses from the QCD sum rules for consistency, where the interpolating currents U a (x), D a (x) and S a (x) are used [31], m Q = 0.46 GeV and m S = 0.40 GeV; the scalar diquarks were originally studied with the QCD sum rules about twenty years ago [32,33]. There have been several theoretical approaches to estimate the diquark masses, for example, the simple constituent diquark mass plus hyperfine spin-spin interaction model [34].…”
Section: Numerical Resultsmentioning
confidence: 99%